2015
DOI: 10.4081/jphr.2015.401
|View full text |Cite
|
Sign up to set email alerts
|

Medical Records Confidentiality and Public Health Research: Two Values at Stake? An Italian Survey Focus on Individual Preferences

Abstract: In a time when Europe is preparing to introduce new regulations on privacy protection, we conducted a survey among 1700 twins enrolled in the Italian Twin Register about the access and use of their medical records for public health research without explicit informed consent. A great majority of respondents would refuse or are doubtful about the access and use of hospital discharge records or clinical data without their explicit consent. Young and female individuals represent the modal profile of these careful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The majority of studies explored attitudes towards the use of health data for research [17,18,[27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44]]. Most studies asked for views regarding research in general [17,18,[27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38],44], while six studies focused on specific registries [[39], [40], [41], [42], [43],45]. Eight studies explored views on the use of data for purposes other than treatment and research, namely the evaluation of a screening programme [46], planning and polic y purposes [32,34,35,44], the production of performance reports [47] and quality assurance (clinical audit ) [48].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies explored attitudes towards the use of health data for research [17,18,[27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44]]. Most studies asked for views regarding research in general [17,18,[27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38],44], while six studies focused on specific registries [[39], [40], [41], [42], [43],45]. Eight studies explored views on the use of data for purposes other than treatment and research, namely the evaluation of a screening programme [46], planning and polic y purposes [32,34,35,44], the production of performance reports [47] and quality assurance (clinical audit ) [48].…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of studies were conducted in the UK [17,18,27,31,[33], [34], [35], [36], [37],[39], [40], [41], [42], [43], [44], [45],47,48,[51], [52], [53]]. Six studies from other countries were identified, including Italy, Germany, Finland, Netherlands and Ireland [[28], [29], [30],38,46,49] and one study was a pan-European survey [50].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we consider worth addressing a few results of research conducted by the ITR on this topic during the last few years. When Europe was just preparing to introduce the new regulation on privacy, we conducted a survey among 1700 twins regarding preferences about the access and use of their medical records for public health research without explicit informed consent (Toccaceli et al, 2015). A great majority of respondents refused or was doubtful about the access and use of hospital discharge records or clinical data without their explicit consent.…”
Section: Ethical and Privacy Issuesmentioning
confidence: 99%